Efficacy and survival of anti-PD-1 antibody in combination with trastuzumab and chemotherapy versus trastuzumab and chemotherapy as first-line treatment of HER2-positive metastasis gastric adenocarcinoma: a retrospective study - Deng, Ting; Li, Danyang; Yang, Yuchong; Wang, Feixue; Bai, Ming; Liu, Rui; Li, Hongli; Ba, Yi (Frontiers in Oncology, 2023)
Background The KEYNOTE-811 study exhibited promising preliminary result for HER-2-positive metastasis gastric adenocarcinoma, however, long-term survival benefit remains to be determined. Methods In this single-center, controlled, retrospective study, patients with histologically confirmed HER2 positive unresectable or metastatic gastric/gastroesophageal adenocarcinoma receiving either PD-1 antibody combined with trastuzumab and chemotherapy (cohort A) or trastuzumab and chemotherapy treatment (cohort B). The primary end points were progression free survival (PFS) and overall survival (OS). The secondary end points were objective response rate (ORR), disease control rate (DCR) and duration of response (DoR). Results A total of 56 patients were eligible to the study with 30 patients in cohort A and 26 patients in cohort B. The median PFS (mPFS) was 16.2 months (95%CI, 15.093-17.307) in cohort A versus 14.5 months (95%CI, 9.491-19.509) in cohort B (P=0.58). The median OS in cohort A was 28.1 months (95%CI 17.625-38.575) verse 31.6 months (95%CI 13.757-49.443) in cohort B(P=0.534). ORR were 66.7% and 50% in two groups respectively. DCR were 90% and 84.6 % in two groups. Median DoR was not reached in cohort A and 16.3 (95% CI, 8.453-24.207) months in cohort B(P=0.141). The most common irAEs were grade 1 hypothyroidism (33.3%) in cohort A. No treatment-related deaths occurred in this study. Conclusions This retrospective cohort study provided a preliminary picture on the long-term follow-up of combining PD-1 antibody with trastuzumab and chemotherapy in HER2-positive GC, a trend with longer DoR and ORR was identified. Further studies with larger sample sizes and deeper molecular investigation are needed.